Vivendo o sistema: uma contribuição para os estudos sobre a aplicação do Sistema de Stanislavski na formação de atores - PARAGUASSU, Renan Delmontt Souza (2021)
This assignment was meant to contribute to studies related to the system of theatrical representation developed by Contantin Stanislavski, in order to understand how to apply the System for interpretation teaching in the actor training, and its possible developments, based on the experience lived in the Teatro e Educação course in the University of Coimbra. It’s intended that the understanding of the theoretical and pratical studies provide to the academic student one more work tool in this area, where its application can be made such by an actor, as a teacher. The search methodology is characterized by a case study, about the experiences in the System training. It has as theoretical reasoning the Constantin Stanilavski’s studies focused on the actor task and its development made by Eugênio Kusnett and Richard Boleslavski. The result of this search allowed me to verify how much the System contributed to provide to the beginner students and actors a solid base to work. Furthermore, this study showed us that’s necessary the theme deepening by the research in other search level, with the possibility of joining it to others teaching methodologies performance.